Development Of Raw Collagen From Waste Mılkfısh (Chanos chanos) Scales As A Preservatıve And Emulsıfyıng Agents - Sudrajat Sugiharta; Euis Prihatini; Iin Lidia Putama Mursal (Politeknik Kaltara, 2023)
Collagen is an essential protein in connective tissue, widely used as a bioactive. Raw collagen is obtained from cattle, buffalo, and pigs with problems spreading infectious animal diseases. Collagen can be obtained from waste milkfish (Chanos chanos) scales as an alternative source of mammal raw materials. This study aims to determine the acetic acid's most effective concentration and maceration time in isolating collagen from milkfish scales based on the preservative and emulsifying determination. This research is quasi-experimental design by testing the isolated collagen against collagen yield, proximate analysis of collagen, pH test, preservative test, and analysis of emulsifier substances. The results of the isolation of collagen in all treatment groups had emulsifying and preservative abilities, where a concentration of 0.5 M acetic acid with a maceration time of 72 hours produced the most effective collagen as an emulsifier based on the results of the emulsion stability test and emulsion layer boundary test, as well as at the concentration of 0, acetic acid 5 M with variations in maceration time of 48 hours and 72 hours produced the most effective collagen as a preservative.